Gerakan Cerdas Lingkungan: Pelatihan Hukum Lingkungan dan Perhitungan Jejak Karbon bagi Siswa SMA - Suryono , Ahmad; Agustina , Lady (LPPM Universitas PGRI Argopuro Jember, 2026)
The development of human activities and technology has a significant impact on increasing carbon emissions, which contribute to climate change. As the next generation, adolescents play a strategic role in maintaining environmental sustainability, but they still face limitations in environmental legal literacy and understanding of their carbon footprint. This community service activity aims to improve ecological literacy, legal literacy, and numeracy skills of high school students through an interdisciplinary approach. The implementation method includes coordination, interactive training, carbon footprint calculation practice, and evaluation through pre- and post-tests. The results of the activity indicate an increase in students' understanding of environmental law, ability to calculate their carbon footprint, and ecological awareness. This program also encourages changes in student behavior towards an environmentally friendly lifestyle. Thus, this activity is effective in developing a young generation that is environmentally conscious, law-abiding, and has analytical skills in addressing climate change issues